Bibliometric Analysis, Primer Design, and AcFT1 Expression of Shallots under In Vitro Multiplication - Rantau, Deritha Ellfy; Noorohmah, Siti; Rahayu, Resa Sri; Syahid, Sitti Fatimah; Hapsari, Betalini Widhi; Wulandari, Dyah Retno; Raihan, Eldrian Daffa; Haz, Aufa Rizqia; Kumala, Ajeng Putri; Yuliawati, Yuliawati; Desriani, Desriani (AGRIVITA Journal of Agricultural Science, 2025)
The use of botanical seeds of shallot as planting materials is more effective than bulbs. However, the characteristics of plants are not ‘true to type’. Bibliometric analysis can identify areas that have been under- explored. Research on biomolecule compounds and gene expression is needed to support biomarker-based detection technology to predict plant productivity early.  This research aims to study the expression of the AcFT1 gene to compare two shallot plantlets with different responses (non-multiplied and multiplied). The AcFT1 gene was identified by bibliometric analysis. GapC2 (group of housekeeping genes) was selected as an internal control gene. The primer designed result were: AcFT1-F: 5’GCGAGAAACCGTCTGCTATGA3’; AcFT1-R: 5’GCAACTGGA GACCCAAGGTT3’; GapC2-F: 5’GCTGCACAACCAACTGCTTA3’; GapC2-R:  5’CCAGTGCTGCTAGGAATGAT3’. The RNA from micro bulb of shallot was then extracted and converted into cDNA with RT-PCR process. Based on the best-optimized PCR annealing temperature (55.2oC), the GapC2 and AcFT1 genes were expressed at the same thickness for both phenotypes, indicating the same level of expression in both micro bulbs. Further, this showed that AcFT1 cannot be used for comparative multiplication studies, this gene is more related to the bulb formation rather than the multiplication process.